Incidental detection of colorectal lesions on 18F-FDG-PET/CT is associated with high proportion of malignancy: A study in 549 patients - Kousgaard, Sabrina Just; Gade, Michael; Petersen, Lars Jelstrup; Thorlacius-Ussing, Ole (Endoscopy International Open, 2020)
Background and study aims Further diagnostics of incidental colorectal lesions on 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) is questionable. Therefore, we aimed to evaluate the clinical importance of incidentally detected colorectal lesions on FDG-PET/CT.Patients and methods In the North Denmark Region, a retrospective study was performed among 19,987 patients who had an FDG-PET/CT from January 2006 to December 2015. Among these patients, we identified patients with a colonoscopy within 12 months from the PET/CT scan and a description of incidental colorectal PET-avid lesions on the PET/CT. PET findings were compared with colonoscopy-detected lesions and eventually histopathology.Results Incidental PET-avid lesions were observed in 549 patients. Colonoscopy revealed lesions in 457 (83 %), among whom 338 patients had a final histopathological diagnosis. Malignant and premalignant lesions were found in 297 patients (54 % among patients with a PET-avid lesion). The lesions were cancer in 76 patients and adenoma in 221 patients of whom 30 had high-grade and 191 low-grade adenomas. The findings changed patient management in 166 cases (30 % of all patients with a PET-avid lesion). A colonoscopy-based surveillance program was initiated for 80 % of patients with high-grade adenoma. No patients with PET-avid lesions but normal colonoscopy developed colorectal cancer during 3 years of observation (median observation time 7 years).Conclusions Incidental colorectal FDG uptake was infrequently observed, but when present, it was associated with a high rate of malignant or premalignant lesions. Our results indicate that patients with incidental colorectal FDG uptake should be referred to diagnostic work-up including colonoscopy.